On scale interactions between the MJO and synoptic scale. (4th November 2018) - Dubey, Sarvesh; Krishnamurti, Tiruvalam Natarajan; Kumar, Vinay
Abstract : DYNAMO was a field experiment conducted over the near‐equatorial Indian Ocean during 2011 and 2012 for a better understanding of the mechanisms of the Madden–Julian Oscillation (MJO). This study uses DYNAMO observations to study the organization of convection and maintenance of the MJO within the framework of synoptic‐scale weather systems. Lorenz box energetics is used over the limited DYNAMO domain to study the in‐scale energetics (i.e. the exchange of energy within a single scale). Formal scale energetics in the frequency domain is used to study the in‐scale as well as out‐of‐scale interactions (i.e. the exchange of energy among diverse scales) of the kinetic energy (KE) and available potential energy (APE) over limited DYNAMO domain and a zonal belt around the Earth extending 20° north and south of the Equator. The synoptic‐scale precipitation distributions, generation of eddy APE (from the covariance of convective heating and temperature) and its disposition to eddy KE (from the covariance of vertical velocity and temperature) confirm the importance of in‐scale energetics for the maintenance of the synoptic scale. The in‐scale energetics in the frequency domain suggest that conversion of APE to KE on the MJO scale is crucial for its maintenance. Out‐of‐scale energetics suggest that over both domains, MJO loses KE to the synoptic time‐scale (2–7 days), but a reverse situation is encountered in the vicinity of the summer subtropical jet. Overall, MJO is found weakly modulating synoptic scales via transferring eddy KE. These results also imply that out‐of‐scale KE interactions between MJO and synoptic scales are not crucial in understanding the maintenance of the MJO over the DYNAMO domain. Abstract : DYNAMO and ERA‐Interim datasets and formal scale energetics in the frequency domain are used to study in‐scale and out‐of‐scale energy interactions between the MJO and synoptic scales. MJO maintains it via available potential energy to kinetic energy transfers and receives noteworthy kinetic energy from the synoptic scale via nonlinear scale interaction only near subtropical jets.